Theoretical aspects of logistics training process management - Palšaitis, Ramūnas; Bazaras, Darius (Transport, 2007)
Authors discuss about main training needs and problems in the logistics as main driving motive for learning and training process organization in the universities and at the non‐formal training places – work places, courses and training organizations. All driving motives can be named as internal and external forces which influence persons. In many cases external driving motives are related to person’s “positive pushing” direction, for example, integration and globalization process in business or implementation of the new technologies. The internal driving motives sometimes are related to problematical points of training, i. e. negative self‐estimation, negative view of environment and bad understanding of knowledge’s benefits in the person’s practical life. The main problems and perspectives of logistics training process are named in this article. Main reasons for training process, methodology and training costs are described. First Published Online: 27 Oct 2010